Nurturing care among adolescent mothers - Tati Sumiati; Sabarinah Prasetyo; Agustin Kusumayati (AOSIS, 2023)
Many studies show the impact of adolescent mothers on child development. To prevent the impact of adolescent pregnancy, nurturing care is needed to support optimal children's development. This study aims to identify comprehensive nurturing care among adolescent mothers. This study used secondary data in the integration of the 2018 National Socioeconomic Survey and Basic Health Survey. To measure nurturing care, 5 components were used: health, adequate nutrition, security and safety, responsive caregiving, and opportunities for early learning with latent class analysis. The results of the analysis showed that 62% of adolescent mothers provided uncompleted nurturing care. About 21% of adolescent mothers need assistance in improving nurturing care related to adequate nutrition and learning opportunities, and 17% need assistance to improve health, nutrition, responsive caregiving, and opportunities for early learning. Adolescent mothers are in need of comprehensive nurturing care for their children. Practice is needed in order to enhance nurturing care initiatives, particularly for teenage mothers.